Pelatihan Dan Pendampingan Pengelolaan Keuangan Wanita Nelayan “Kelompok Pengolah Dan Pemasaran Hasil Tangkapan”: Upaya Meningkatkan Literasi Keuangan Di Desa Tasikmadu - Eliza Silviana Miftakh (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Training and accompaniment in the financial management of female fishermen in catch processing and marketing groups by accounting lecturers has a significant role in increasing financial literacy in Tasikmadu Village, Prigi, Trenggalek Regency. This community service article discusses the importance of efforts to increase financial literacy. Accounting lecturers provide training on financial management and accounting practices to the Catch Processing and Marketing Group, as well as providing guidance in applying these concepts in daily business operations. Apart from that, lecturers can introduce financial management guidebooks, accounting applications and help business groups understand financial records and create accountable financial reports. The positive impacts include increasing economic prosperity, reducing business risks, sustainable growth, contributing to local economic growth, and improving the overall community economy.